Enhanced Mechanical Stability and Biodegradability of Ti-Infiltrated Polylactide - Viet Phuong Nguyen; Yoo, Jin; Lee, Ju Young; Chung, Justin J.; Hwang, Jeong Ho; Jung, Youngmee; Lee, Seung-Mo (American Chemical Society, 2020)
Biodegradable polymers have been often used in place of conventional nondegradable polymers for industrial and medical applications. In particular, polylactide (PLA) has been regarded as a popular ecofriendly plastic and has many advantages like good biocompatibility and processability. Yet, it still has some drawbacks in mechanical properties. Here, we prepared Ti-infiltrated PLA by mimicking the gelatinous jaw of a seaworm whose mechanical properties are toggled up and down by the tiny amount of metal ions, expecting to prepare a new type of alternative. Ti induced significant chemical and microstructural changes in the PLA, which led to a notable improvement in the mechanical properties as compared to the neat PLA. The Ti-infiltrated PLA exhibited high resistance to rapid degradation. More importantly, the toxicity assessment demonstrated that the resulting PLA is still biocompatible and nontoxic. Consequently, we proved that the Ti-infiltrated PLA has high mechanical properties comparable to conventional nondegradable polymers and good biocompatibility as well as delayed biodegradability. We anticipate the current Ti-infiltrated PLA to be an ecofriendly replacement of some conventional plastics, which helps preserve a green environment.
Keywords: MASSIVE POLY(ALPHA-HYDROXY ACIDS); HYDROLYTIC DEGRADATION; COMPOSITES; BLENDS; NEREIS; ZINC; PLA